The Role of Nurse Mentoring in Enhancing Nursing Students’ Clinical Competence -A Cross-Sectional Study - Asmirajanti, Mira; Novitasari, Nadia (Jurnal Berita Ilmu Keperawatan, 2026)
Clinical practice is an essential component of nursing education, aimed at developing students’ competencies in real healthcare settings. The role of clinical nurse mentors is a key external factor influencing the success of students in achieving clinical competence. This study aimed to analyze the correlation between nursing students’ perceptions of nurse mentoring and their clinical competence achievement. This type of research is quantitative correlative analytic with a cross-sectional research design, namely by measuring variables at a certain time. The sample consisted of 82 nursing students from University A who had completed their clinical practice, selected through purposive sampling. Research instruments included a questionnaire on students’ perceptions of nurse mentoring and a clinical competence achievement questionnaire. Data analysis was performed using the Spearman correlation test. The results showed that most students had a positive perception of nurse mentoring (86.6%) and achieved clinical competence in the "good" category (93.9%). A significant relationship was found between students’ perceptions of nurse mentoring and their clinical competence (r = 0.698; p < 0.05), with the evaluation domain showing the strongest correlation (r = 0.650). These findings suggest that the more positive students’ perceptions of their clinical mentors, the higher their level of clinical competence. Associating the role of clinical mentors through training and ongoing evaluation is essential to support effective learning outcomes in nursing clinical education.